2020
DOI: 10.1590/1414-431x20209816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative overview of the effects of aerobic and resistance exercise on anxiety-like behavior, cognitive flexibility, and hippocampal synaptic plasticity parameters in healthy rats

Abstract: Clinical studies show that physical exercise has anxiolytic and pro-cognitive properties for both healthy individuals and psychiatric patients. Most of these data refer to the effects of aerobic exercise. However, other modalities such as resistance exercise deserve more attention because they may also modulate brain function. This study aimed to compare the effects of an aerobic exercise protocol on a treadmill and a resistance exercise protocol on a ladder apparatus on anxiety-like behavior, cognitive flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Also increase in both central and peripheral IGF-1 levels following exercise training in rodents (Carro et al, 2000;Trejo et al, 2001;Nakajima et al, 2010;Kim et al, 2019) have been reported. Finally, IGF-1 increases the expression of BDNF (Carro et al, 2000), synaptic plasticity markers such as synaptophysin and postsynaptic density protein-95 in the hippocampus, and represents positive effects on the spatial and aversive memories in healthy rats (Segabinazi et al, 2020).…”
Section: Insulin-like Growth Factor-1mentioning
confidence: 96%
“…Also increase in both central and peripheral IGF-1 levels following exercise training in rodents (Carro et al, 2000;Trejo et al, 2001;Nakajima et al, 2010;Kim et al, 2019) have been reported. Finally, IGF-1 increases the expression of BDNF (Carro et al, 2000), synaptic plasticity markers such as synaptophysin and postsynaptic density protein-95 in the hippocampus, and represents positive effects on the spatial and aversive memories in healthy rats (Segabinazi et al, 2020).…”
Section: Insulin-like Growth Factor-1mentioning
confidence: 96%
“…In this study, the classical ethological test for anxiety/depression was used to evaluate mental disorders in rats. The light-dark box, the elevated plus-maze, and the open-eld tests are classic ethological tests for anxiety evaluation [28][29] . NP exposure led to an increase in the residence time in the light-dark box test, the frequency of entry into the closed arm of the elevated plus maze test, while the rat immobility time in the central square in the open eld test was reduced, which suggested that the rats lost interest in exploring external objects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced object recognition memory and cognitive flexibility were seen in exercised adult and old mice. Similarly, Segabinazi and colleagues [ 58 ] showed that adult rats previously exposed to a six-week period of aerobic training did not exhibit any improvement when evaluated for cognitive flexibility.…”
Section: Aerobic Exercise Effects On Cognitive Functions and Neural S...mentioning
confidence: 98%